2017
DOI: 10.1021/acsomega.7b00431
|View full text |Cite
|
Sign up to set email alerts
|

Effective Adsorption of Precious Metal Palladium over Polyethyleneimine-Functionalized Alumina Nanopowder and Its Reusability as a Catalyst for Energy and Environmental Applications

Abstract: Palladium is one of the widely used precious metals toward catalysis, energy, and environmental applications. Efficient recovery and reusability of palladium from the spent catalysts is not only highly desirable for sustainable industrial processing but also for preventing environmental contamination. Here, we present a facile citrate-mediated amine functionalization of alumina nanopowder (AO) in aqueous medium. The surface functionalization is probed using infrared (IR), X-ray photoelectron spectroscopy (XPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…By plotting a relation between C e /q e against C e , a straight line was obtained with a slope equals to 1/q m and an intercept equals to 1/bq m . The q m of Pd 2+ equals 198.2 mg g −1 which is higher than that achieved by other sorbents [ 10 , 39 , 40 , 41 ] as shown in Table (2) . The results also showed that RH@MCM-41@ARS had greater q m compared to that of RH@MCM-41 and RH (16.1 and 13.3 mg g −1 , respectively).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…By plotting a relation between C e /q e against C e , a straight line was obtained with a slope equals to 1/q m and an intercept equals to 1/bq m . The q m of Pd 2+ equals 198.2 mg g −1 which is higher than that achieved by other sorbents [ 10 , 39 , 40 , 41 ] as shown in Table (2) . The results also showed that RH@MCM-41@ARS had greater q m compared to that of RH@MCM-41 and RH (16.1 and 13.3 mg g −1 , respectively).…”
Section: Resultsmentioning
confidence: 64%
“… Method q m (mg g −1 ) Ref. Polyethyleneimine-Functionalized Alumina Nanopowder 97.7 [ 39 ] Poly (N-phenylethanolamine) modified MWCNTs 101 [ 40 ] Cellulose filter paper grafted with polymer chains bearing thiocarbamate moieties 37 [ 41 ] Modified activated carbon 92 [ 10 ] RH@MCM-41@ARS 198.2 Our work …”
Section: Resultsmentioning
confidence: 99%
“…Here, oxygen‐containing groups might serve as mediators between the electrode and the electroactive species 32 . Moreover, RVC has a higher binding energy because of the bonding with oxygen atoms 33 . Pd and Sn in Shipley's solution provide catalytic sites on the substrate for metal nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…32 Moreover, RVC has a higher binding energy because of the bonding with oxygen atoms. 33 Pd and Sn in Shipley's solution provide catalytic sites on the substrate for metal nucleation. Yap (2009) found that Shipley's solution gives better performance in the gold deposition process on RVC, based on her morphological analysis on RVC after activation with Shipley's solution.…”
Section: Effect On Cathode Activationmentioning
confidence: 99%
“…The increase in adsorption capacity at equilibrium with respect to the initial Eu­(III) concentration is attributed to the fast and effective interaction between Eu­(III) and the surface of the biosorbent . The maximum Langmuir adsorption capacity was calculated through the plot of C e / q e against C e (Figure b), with the linear form of the equation as where C e (mg L –1 ) and q e (mg g –1 ) refer to the equilibrium concentration and the amount of Eu­(III) adsorbed at equilibrium, respectively. q o (mg g –1 ) is the maximum adsorption capacity, and b (L mg –1 ) is the Langmuir constant related to the energy of adsorption.…”
Section: Resultsmentioning
confidence: 99%